Valuing goat genetic resources: a pro-poor growth strategy in the Kenyan semi-arid tropics - Omondi, Immaculate A.; Baltenweck, Isabelle; Drucker, Adam G.; Obare, G.A.; Zander, K.K. (Springer, 2008)
Goats, “the poor man’s cow”, provide very important genetic resources that can be exploited for continued improvements of the livelihoods of poor livestock keepers in the semi-arid tropics. This study presents the evaluation of the economic values of goat genetic resources (GGRs) in terms of the important non-market traits embedded in goats and how this information can be utilised to improve livelihoods in semi-arid regions. The results obtained from mixed logit models derived from stated choice data collected from 314 respondents in the semi-arid Marsabit district of Kenya reveal that disease resistance is the most highly valued trait whose resultant augmentation results into a welfare improvement of up to KShs.2899. Drought tolerance and milk traits were found to be implicitly valued at KShs.2620 and 1179 respectively. The study further revealed that improvement in milk trait in does, body size and disease resistance traits in bucks, and drought tolerance trait in both does and bucks will collectively improve the producers’ welfare hence should be given priority. However, improvement in the reproduction and production (“overall body condition/ meatiness” trait) potential of goats will be worthwhile only if issues concerning access to pasture and water resources are addressed prior and simultaneously.